2021
DOI: 10.21203/rs.3.rs-135048/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coalescence Dynamics in Oil-In-Water Emulsions at Elevated Temperatures

Abstract: Emulsion stability in a flow field is an extremely important issue relevant for many daily-life applications such as separation processes, food manufacturing, oil recovery etc. Microfluidic studies can provide micro-scale insight of the emulsion behavior but have primarily focussed on droplet breakup rather than on droplet coalescence. The crucial impact of certain conditions such as increased pressure or elevated temperature frequently used in industrial processes is completely overlooked in such micro-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Radzi (2016) noted that the viscosity of both the oil and water phase and surface tensions were reduced at higher temperatures. Hasan et al (2010) studied the effect of temperature on the viscosity of heavy crude oil, and they observed a reduction in viscosity from 10 to 6.3 Pa•s when the temperature was increased from 25 to 75 • C. Furthermore, Bera et al (2021) investigated the coalescence between oil droplets and observed higher coalescence frequencies at elevated temperatures (from 20 to 70 • C). Sadeghi and Vissers (2020) used a laboratory scale flotation unit to investigate the effect of temperature on bubble size, and they found that the increase in temperature slightly reduced the size of large bubbles from 96 to 81 μm; however, it did not have significant effect on small bubbles (20 μm).…”
Section: Temperaturementioning
confidence: 99%
“…Radzi (2016) noted that the viscosity of both the oil and water phase and surface tensions were reduced at higher temperatures. Hasan et al (2010) studied the effect of temperature on the viscosity of heavy crude oil, and they observed a reduction in viscosity from 10 to 6.3 Pa•s when the temperature was increased from 25 to 75 • C. Furthermore, Bera et al (2021) investigated the coalescence between oil droplets and observed higher coalescence frequencies at elevated temperatures (from 20 to 70 • C). Sadeghi and Vissers (2020) used a laboratory scale flotation unit to investigate the effect of temperature on bubble size, and they found that the increase in temperature slightly reduced the size of large bubbles from 96 to 81 μm; however, it did not have significant effect on small bubbles (20 μm).…”
Section: Temperaturementioning
confidence: 99%
“…Hasan et al (2020) studied the effect of temperature on the viscosity of heavy crude oil, and they observed a reduction in viscosity from 10 Pa•s to 6.3 Pa•s when the temperature was increased from 25 °C to 75 °C. Furthermore, Bera et al (2021) investigated the coalescence between oil droplets and observed higher coalescence frequencies at elevated temperatures (from 20 °C to 70°C). Sadeghi and Vissers (2020) used a laboratory scale flotation unit to investigate the effect of temperature on bubble size, and they found that the increase in temperature slightly reduced the size of large bubbles from 96 μm to 81 μm; however, it did not have significant effect on small bubbles (20 μm).…”
Section: Phmentioning
confidence: 99%